2002
DOI: 10.1063/1.1507577
|View full text |Cite
|
Sign up to set email alerts
|

Field-independent grating formation rate in a photorefractive polymer composite sensitized by CdSe quantum dots

Abstract: The rate of grating formation in a photorefractive polymer composite sensitized by CdSe quantum dots is found to be independent of applied field, in contrast to similar composites sensitized by other types of nanoparticles. The photorefractive polymer composite under study consists of poly(N-vinylcarbazole) as the nominal charge transporting matrix, an electro-optic dye, and CdSe quantum dots passivated by tri-n-octylphosphine oxide. Both the field-independent grating formation rate and the lower diffraction e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
0
19
1
Order By: Relevance
“…A low value of ionized nanoparticles, N 0 limits the space-charge field that can be produced within the material and hence reduces the optical efficiency. For small N 0 and assuming Langevin recombination, the response time s sc of the space-charge field in an optical material is given by [28] s sc ¼…”
Section: Discussionmentioning
confidence: 99%
“…A low value of ionized nanoparticles, N 0 limits the space-charge field that can be produced within the material and hence reduces the optical efficiency. For small N 0 and assuming Langevin recombination, the response time s sc of the space-charge field in an optical material is given by [28] s sc ¼…”
Section: Discussionmentioning
confidence: 99%
“…However, a relatively thin shell of the small molecule 4-methylbenzenethiol was ascribed to present only a thin barrier to charge transfer between host and QD, which resulted in astonishing fast PR-response [ 133 ] (see Table 3 ). Contrarily, the direct comparison of 1-hexadecylamine (HDA) capped CdSe QD [ 134 ] yielded two orders of magnitude higher sensitivity compared to tris-n -octylphosphine oxide (TOPO)-capped CdSe particles, [ 141 ] the former molecule forming the thicker capping. Photoluminescence studies on both particles exhibited bathochromic shifted spectral features regarding the excitonic peak for TOPO capped CdSe QD only, which indicates the presence of detrimental charge traps on the dot surface.…”
Section: Metal-atom Containing Complexes As Sensitizersmentioning
confidence: 99%
“…[ 111 , 154 , 155 ] In a combined Figure 11 . Semi logarithmic plot of the sensitivity of identical composites with sensitizer made from CdSe/ZnS [ 136 ] (squares), CdSe/CdS [ 135 ] (circles) and CdSe core-only [ 141 ] (all TOPO-capped) QDs, plotted against the applied electric fi eld. The sensitivity is evaluated according to S = Δ n / τ I α .…”
Section: Co-sensitizationmentioning
confidence: 99%
“…CdS [5], HgS and PbS [6] nanoparticle sensitization has been reported but CdSe nanoparticles have been the most commonly used in PPCs because the band gap of CdSe is conveniently located in the visible part of the spectrum. PPCs incorporating CdSe nanoparticles with a CdS shell [7] and a variety of surface ligands [8][9][10] have been investigated recently, demonstrating a considerable range in performance. In particular, recent work has shown that enhanced photorefractive performance can be achieved by careful selection of the ligand [10].…”
Section: Introductionmentioning
confidence: 99%